A relationship between physical activity and healthy quality of life in students - Ali Ashkanı; Amin Azımkhanı; Mahdi Talebpour; Masoud Aghaeı; Sadegh Abbasıan (Türk Spor ve Egzersiz Dergisi)
The purpose of this research is to relationship between physical activity and healthy quality of life in students. Statistical population of this research involves all physically active male students in Iran from which 1352 students participated in the study as sample by using cluster sampling and sample random method. Collection data tools of this research were  questionnaire according to its nature: Sharkey Physical Activity Questionnaire and Life Quality Questionnaire (WHOQOL-BREF, 2204) were used after consultation to professors, guidance and advice of authorities. As all respondents were students BREF type was selected, including four aspects of life quality plus two general questions about life and health quality evaluation. Reliability of Physical Activity Questionnaires was r = 0.91. Inferential statistics (Correlation coefficients) was also used. Results showed that there was a low significant relationship between participation in sport activities and physical health in active students (r= 0.38, p= 0.000). There was a low significant relationship between participation in sport activities and mental- psychological condition in active students (r= 0.27, p= 0.003). In case of social communication, there was a low significant and positive relationship between participation in sport activities in active students (r= 0.32, p= 0.000). There was a low significant relationship between participation in sport activities and environmental domain in active students (r= 0.05, p= 0.62). There was a low significant relationship between participation in sport activities and life quality in active students (r= 0.24, p= 0.008). In conclusion, performing sport activities during leisure time has physical benefits, and also effective influences on overcoming mental problems. As well as invulnerability to many diseases and disorders, those who train regularly enjoy disciplined life, more performance and social relationships by acquiring freshness and further enjoy of life.